A Fluorescence Probe for "Turn‐Off" Heavy‐Metal‐Ion Sensing – Synthesis and Characterization of a Dipyrromethene p‐Phenylenevinylene Conjugated Copolymer and Its Electronic and Optical Properties. Issue 13 (3rd April 2023) - Joseph, Alex; Mathai, George; Schwandt, Carsten; Ramamurthy, Praveen C.; Subramanian, Sankaran
Abstract: Fluorescent electroactive polymers possess good transduction properties and are used as active materials for sensors. Here, a fluorescent conjugated copolymer has been synthesized from dipyrromethane and p‐phenylenevinylene as the monomers, and characterized for its optical and sensing properties. Absorption and emission analyses in various solvents have shown that the polymer exhibits excellent solvatochromism. A DFT method has been used to predict the bandgap as well as the electron distributions in HOMO and LUMO levels. The interaction of the polymer with selected metal ions has been studied in different solvents and the change in emission with concentration of the analyte has been determined. It has been observed that the polymer has a significant affinity towards Fe 2+, Fe 3+ and Co 2+ ions with high Stern‐Volmer quenching constants. Overall, this work has demonstrated that the polymer synthesized has a potential application as a heavy metal ion turn‐off sensor. Abstract : Fe2+/3+ and Co2+ heavy metal ions are sensed using a dipyrromethene p‐phenylenevinylene conjugated copolymer in THF. The coordination of the metal results in the quenching of emission and the quenching properties are assessed by measuring emission intensities.